Correlation of cervical cancers with long-term use of hormonal oral contraceptive pills - A retrospective observational multicentric study in suburban-based medical colleges in West Bengal - Partha Sarathi Mitra; Medhatithi Barman; Pramit Goswami; Jayita Saha; Debjit Saha (Asian Journal of Medical Sciences, 2023)
Background: Hormonal oral contraceptive pills (OCP) may increase the risk of carcinoma cervix by changing the susceptibility of cervical cells to persistent infection with high-risk human papilloma virus. There is a causal and promoting association with long-term use of these pills for more than 5 years of use, and the association is diminished 10 years after last use. Aims and Objectives: In this study, retrospective data were collected to analyze the risk of association of carcinoma cervix with hormonal contraceptive pill use. Materials and Methods: Interview-based retrospective observational study to enquire about the history of hormonal OCP use and duration of intake in all diagnosed cases of cervical carcinoma attending gynecology and oncology outpatient departments over the period of 2 years in two medical colleges in suburban West Bengal. Results: Of the total 401 subjects, 119 have a history of intake of hormonal OCPs, and 198 have a history of other methods of contraception. Among the subjects, 67.58% had squamous cell carcinoma (SCC), 31.67% had adenocarcinoma of the cervix, and 0.75% had other varieties. There is no correlation between the duration of hormonal OCP use and SCC cervix (P=0.269), whereas there is a significant correlation between adenocarcinoma of the cervix and duration of intake of hormonal OCP (P=0.002). Conclusion: Studies have shown that women who have used OCPs for 5 or more years have a higher risk of cervical cancer than women who have never used oral contraceptives. This study reported a statistically significant increase in the relative risk of adenoca of the cervix but not of the SCC of the cervix, even after long-term use of hormonal OCPs.